Determinants of Managerial Skill Spillover from FDI Enterprise to SMEs Vietnam - Thi Huong, Dang (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2018)
This paper investigates the determinants of managerial skill spillover from FDI enterprise to SMEs Vietnam. By using expert interviewing method and survey, the paper initially identifies and evaluates factors affecting the transfer of managerial skills from FDI enterprises to SEMs in Vietnam. These factors include: Attitude and willingness to receive the spillover; Managerial capacity; Spillover channels and environment supporting spillover. Based on the results, the paper proposes some suggestions to promote the transfer of managerial skills from FDI enterprises into SMEs in Vietnam.